The Effect of Teacher Discipline and Learning Interest on Student Achievement - Apriyanto, Tri; Ulfi Fadli, Muhammad (Universitas Muhammadiyah Jember, 2025)
Write the The study is a quantitative correlation with linear regression analysis dealing with three independent variables and one dependent variable to know links between variables through numerical data obtained from field research. The sample was 20,10%, with 80 students from the total population of 398 students in SMP Nida Al-Qur’an Kedu Temanggung. Data collection uses library study methods, documentation and questionnaires. Data processing techniques use SPSS for classic assumptions statistical tests F and T. Teacher discipline and interest in learning are assessed according to a perspective based on indicators from experts and student achievement using indicators measuring student achievement in the form of numerical values ​​taken from curriculum merdeka report cards. So the results obtained were that teacher discipline and interest in learning had a positive effect of 69.5% on student achievement in Islamic Religious Education Lessons SMP Nida Al-Qur’an Kedu simultaneously based on the calculated F count greater than the F table value (87,662 > 3,114), strengthened by sig. value 0.000 < 0.05. Teacher discipline has a positive effect on student achievement in Islamic Religious Education Lessons SMP Nida Al-Qur’an Kedu strengthened by sig. value 0.000 < 0.05. and the t count is 2.905 > t table 1,665. Interest in learning has a positive effect on student achievement in Islamic Religious Education Lessons SMP Nida Al-Qur’an Kedu with a significance value of 0.000 < 0.050, and the t count is 6,111 > t table is 1,665.